THE SILENT COMMITMENT: UNVEILING THE INVISIBLE WORK OF MANAUS MUNICIPAL EDUCATORS - do Nascimento, Elka Maria Freitas; Garcia, Elenilson de Sena; Nogueira, Francisco dos Santos; de Freitas, Priscila Lima; Cunha, Silvângela da Silva; Braga, Stela Mary N.; Coelho, Welhington dos Santos (Seven Editora, 2025)
This article unveils the paradox of institutional invisibility faced by municipal teachers in Manaus. Analyzing the tireless dedication of these professionals in contrast with the lack of effective recognition from managers, the study argues that chronic devaluation manifests through the overload of functions (social suppliance) and grave health consequences. The research quantifies teacher illness—especially the high rates of burnout—and critically discusses the underreporting of medical leaves, which masks the real extent of suffering. It is concluded that valuation is not an act of courtesy, but a strategic imperative for the sustainability of public education, whose pillars are invisibly supported by the efforts of these educators.DOI: https://doi.org/10.56238/sevened2025.038-005